Deploying Open Source IP Telephony in Rural Environments - Lambrinos, Lambros (My University, 2008)
In the current era of advanced telecommunications and the Voice-over-IP revolution, areas lacking modern telephony facilities are still commonplace. In this paper we propose an architecture that utilises open source software and other technologies to provide enhanced telephony services in a rural community. Using a wireless network infrastructure we interconnect our SIP-based telephony exchange with the IP phones and the adaptors installed at various locations enabling seamless internal communication. Connectivity to the normal telephone network is facilitated through a satellite link and a number of analogue lines. A pilot implementation has provided some interesting findings and pinpointed some issues. We discuss potential ways of resolving those issues and enhancing our infrastructure even further.